Improving outcomes of patients living with psoriatic arthritis: The Observational Best Practices Research Initiative (OBRI-PsA) registry: Rationale, Methodology and Preliminary Data of 18 Months Follow-up - Rahaf Zyad Attar; Mohammad Movahedi; Angela Cesta; Xiuying Li; Ricardo Sabido-Sauri; Ozun Bayindir Tsechelidis; Arthur Lau; Andrew Chow; Carter Thorne; Derek Haaland; Elaine Soucy; Claire Bombardier; et al. (PLoS ONE, 2026)
Objectives Psoriatic arthritis (PsA) is a heterogeneous, chronic inflammatory disease with diverse musculoskeletal and extra-articular manifestations, including enthesitis and dactylitis, which contribute substantially to disease burden, disability, and poor quality of life. Therapeutic advances have mainly focused on polyarticular disease, with limited representation of other PsA domains and real-world complexity. The Observational Best Practices Research Initiative for Psoriatic Arthritis (OBRI-PsA) was established as a national registry to systematically capture diverse PsA phenotypes, assess real-world treatment patterns, and longitudinal clinical outcomes. This report describes the registry methodology and presents preliminary findings from the initial enrolled cohort. Methods OBRI-PsA is actively enrolling patients with active PsA initiating new disease-modifying therapy, irrespective of domain or burden. Baseline and follow-up data are systematically collected to evaluate treatment responses, patient-reported outcomes, productivity, and real-world strategies. Descriptive analyses of 18-month outcomes from the first 101 enrolled patients are presented as a proof-of-concept; the full study protocol is available in the supplementary material. Results As of September 2024, a total of 101 patients were enrolled (mean age 53.9 ± 12.7 years; 61.4% female). Symmetrical polyarthritis predominated (86.1%), with 91% having skin psoriasis, 49% enthesitis, and 42% dactylitis. At baseline, mean tender and swollen joint counts were 9.8 and 6.5. Over 18 months, patient- and physician-reported outcomes improved, yet only one-third achieved minimal disease activity (MDA). Response rates varied across domains, with the lowest rate observed for enthesitis (24%). Most patients (60–74%) remained on the same therapy at follow-up with no further modifications, despite ongoing disease activity. Patients with fibromyalgia reported higher disease activity, lower quality of life, and fewer treatment responses. Conclusion Preliminary data from OBRI-PsA highlight persistent unmet needs and variable treatment responses across PsA phenotypes in real-world practice, with relatively few patients achieving treatment targets. These early signals underscore the importance of a comprehensive, longitudinal registry platform to better characterize disease heterogeneity and to inform future phenotype-driven, outcome-focused analyses.